The gut–brain axis in irritable bowel syndrome: neuroendocrine and epigenetic pathways - Lemonica Koumbi; Maria-Anna Giannelou; Lorys Castelli (Academia Biology)
Irritable bowel syndrome (IBS) is a complex disorder arising from gut–brain axis (GBA) dysfunction, where psychological distress, immune dysregulation, and gut microbiota imbalances interact to shape symptom development. Neurotransmitters and hormones play pivotal roles in mediating visceral sensitivity, gut motility, and emotional processing, linking IBS to neuropsychiatric conditions. Chronic hypothalamic–pituitary–adrenal (HPA) axis overactivation disrupts cortisol and norepinephrine balance, exacerbating intestinal permeability and inflammation. Serotonin, histamine, and dopamine further modulate pain perception, stress responses, and gut function, while sex hormones contribute to IBS’s sex-based prevalence. Gut microbiota alterations influence neurotransmitter metabolism and immune responses, perpetuating a cycle of stress-induced gut dysfunction. Emerging epigenetic modifications highlight long-term gene expression changes linked to early-life stress and microbiota shifts. Understanding IBS as a stress-sensitive, neuroimmune metabolic disorder necessitates integrative approaches, combining microbiome-targeted therapies, stress management, and precision medicine to improve symptom outcomes.